CyTest – An Innovative Open-source Platform for Training and Testing in Cythopathology. (20th July 2016) - Lianas, Luca; Piras, Marco Enrico; Musu, Elodia; Podda, Simona; Frexia, Francesca; Ovcin, Emanuela; Bussolati, Giovanni; Zanetti, Gianluigi
Abstract: This paper describes an e-learning platform developed in the context of the European Project CyTest (2014-1-IT01-KA202-002607), dedicated to Cytological Training at European Standard through Telepathology. The main, and novel, feature of our system is the deep integration between virtual microscopy and the training system: images are not simply there to be seen but they are active parts of testing, supporting quantitative measurement of image comprehension, for instance by evaluating the identification of relevant cellular structures by the position of markers put by the student on the image. The solution we developed offers a complete tool for easy creation and interactive access to questions related to images and fully integrates the components of virtual microscopy and teaching, based on state-of-the-art instruments for digital pathology images management, as OMERO, and for training course distribution, as Moodle. The system can be easily extended to support histopathological diagnosis. The software is distributed as Open Source and available on GitHub.